(3eLehY COHjs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg eG CMSf ehbY JYbH GdTGYQ aj HjJ jbhdg hojTJgQ Yfg, hjJeKd Hg dUMI eYfGg, HeG gh CUOb s
(3BNQgG (B:s
(3bjd(B: (3aeG jWdHhf? bGd GdQGMI, hPdc eG dG jchf habfG Gddg deG ajg QGMI GdBNQI s
(3GdNW ajg VHW heged GdfbW CMjGfkGs
(3fbhd ef GdTYQ hGdfKQs
(3ef OhGhjf hcJH dTYQGA aj eNJda GdYUhQ NGUI GdYUQ GdYHGSj heG HYOgs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs